2021
DOI: 10.3390/biom11010106
|View full text |Cite
|
Sign up to set email alerts
|

From Cell Culture to Organoids-Model Systems for Investigating Prion Strain Characteristics

Abstract: Prion diseases are the hallmark protein folding neurodegenerative disease. Their transmissible nature has allowed for the development of many different cellular models of disease where prion propagation and sometimes pathology can be induced. This review examines the range of simple cell cultures to more complex neurospheres, organoid, and organotypic slice cultures that have been used to study prion disease pathogenesis and to test therapeutics. We highlight the advantages and disadvantages of each system, gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 131 publications
0
7
0
Order By: Relevance
“…Refinement, reduction and replacement (“3R”) of animal studies is desirable due to ethical reasons but also towards less cost and labour-intensive methods, therefore alternatives to bioassays such as versatile cell culture models are needed. Already early in prion research a first persistently infected cell line from mouse was established 7 , later further cell models were introduced (for review see 8 ). One successful example of a bioassay alternative is the standard scrapie cell assay based on subcloned neuroblastoma N2a cells, which was developed for titre determination of murine scrapie (22L and RML) reaching equal sensitivity while being significantly faster and cheaper 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refinement, reduction and replacement (“3R”) of animal studies is desirable due to ethical reasons but also towards less cost and labour-intensive methods, therefore alternatives to bioassays such as versatile cell culture models are needed. Already early in prion research a first persistently infected cell line from mouse was established 7 , later further cell models were introduced (for review see 8 ). One successful example of a bioassay alternative is the standard scrapie cell assay based on subcloned neuroblastoma N2a cells, which was developed for titre determination of murine scrapie (22L and RML) reaching equal sensitivity while being significantly faster and cheaper 9 .…”
Section: Introductionmentioning
confidence: 99%
“…One successful example of a bioassay alternative is the standard scrapie cell assay based on subcloned neuroblastoma N2a cells, which was developed for titre determination of murine scrapie (22L and RML) reaching equal sensitivity while being significantly faster and cheaper 9 . However, this assay only works for mouse-adapted scrapie strains, which is a common problem of most cell culture models: being limited to certain host-adapted prions only 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…To verify our findings, we established RK13 cell lines that stably expressed WT, ΔN6, or Met4-1 PrPs. RK13 is a rabbit kidney epithelial cell line that expresses little endogenous PrP and has been widely used to determine the susceptibility of various PrP forms to prion infection ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since N2a neuroblastoma cell line is susceptible to prion infection (37), we used it as a positive control and found that the cellular localization of transfected PrPs were similar to J o u r n a l P r e -p r o o f that of endogenous PrP in N2a cells (Supporting Fig. S1).…”
Section: Expression Of Wt Met4-1 and ∆N6 Prps In Rk13 Cellsmentioning
confidence: 99%
“…One successful example of a bioassay alternative is the standard scrapie cell assay based on subcloned neuroblastoma N2a cells, which was developed for titre determination of murine scrapie (22L and RML) reaching equal sensitivity while being significantly faster and cheaper [9]. However, this assay only works for mouse-adapted scrapie strains, which is a common problem of most cell culture models: being limited to certain host-adapted prions only [10,8].…”
Section: Introductionmentioning
confidence: 99%